The depiction of the US-China relations and Chinese culture in American cinematography - Novosad, Matěj; Rolenc, Jan Martin, 1980-; Garlick, Jeremy; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
In my thesis, I set out to conduct an Interpretative Discourse Analysis of three selected movies. I focused on the depiction of Chinese and American identities in the movies through the lens of Edward Said´s Orientalism. Through my work I wanted to showcase how China, through its influence on Hollywood, counters Orientalism and to sum degree executes a form of Occidentalism.
Vedoucí práce: Jan Martin Rolenc
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses